The fifth domain : defending our country, our companies, and ourselves in the age of cyber threats - Clarke, Richard A. (Richard Alan), 1951-; Knake, Robert K (Penguin Press, 2019)
Presents an urgent assessment of how governments, businesses, and everyday citizens can counter and prevent attacks by criminal hackers determined to create a digital war zone.